Islamic legal system in Malaysia: an Introduction - Wan Muhammad, Ramizah (Islamic Book trust, 2025)
Islamic legal system in Malaysia: an Introduction succinctly describes the functioning of Islamic legal system in Malaysia. Issues such as position of Islam in the Federal Constitution of Malaysia and the role of specific Islamic institutions in Malaysia are illuminated. The book explains in clear terms the jurisdictional powers of the Syariah Court, the institutions of fatwa, the role of the Syarie Counsel and the authority of the Syarie judge. This renders the book a unique and significant contribution for law students, particularly for the subject of Islamic Legal System (SHAS 1350) in Ahmad Ibrahim Kulliyyah of Laws (AIKOL), IIUM. This book is also an accessible text to non-specialists interested in matters pertaining to Islamic legal system in Malaysia.